The BL-Lac gamma-ray blazar PKS 0447-439 as a probable member of a group of galaxies at z = 0.343 - Muriel, Hernan (2015)
Context. The BL-Lac blazar PKS 0447-439 is one of the brightest HE gamma-ray sources that were first detected by Fermi-LAT. It was also detected by H.E.S.S. at VHE gamma-rays, which allowed constraining the redshift of PKS 0447-439 by considering the attenuation caused by gamma-ray interactions with ambient photons in the extragalactic background light (EBL). This constraint agreed with color-magnitude and spectroscopic redshift constraints (0.179 <z< 0.56). Recently, however, a much higher redshift was proposed for this blazar (z> 1.2). This value was debated because if true, it would imply either that the relevant absorption processes of gamma-rays are not well understood or that the EBL is dramatically different from what is believed today. This high redshift was not confirmed by three independent new spectroscopic observations at high signal-to-noise ratios. The scenario is clear evidence of the difficulties in estimating the redshift of BL-Lac objects, whose optical spectra are typically featureless. Neither of the estimated redshifts for PKS 0447-439 are confirmed as yet.